SOCIAL SECURITY AND WELL-BEING IN A LOW-INCOME ECONOMY: AN APPRAISAL OF THE KERALA EXPERIENCE - HIROSHI SATO (The Developing Economies, XLII-2 (June 2004): 288-304, 2004)
The State of Kerala, which is considered to have attained a level of social well-being comparable to that of advanced countries despite its relatively low income standard, is widely known as an example of "welfare by public intervention" in developing economies. This paper, focusing on the four areas of food provision, health services, elementary education, and pension schemes, and paying attention to the participation of the private sector as well as the activities of political parties and labor unions, points out that in Kerala, the private sector and organized activities have played a vital role, in addition to "public intervention," in the betterment of public welfare.